Comics in The Classroom : A Study On Improving Students' Creative Reading Literacy in Indonesian Language Learning - Ariesty Fujiastuti; Purwati Zisca Diana (Jurnal Kependidikan: Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran dan Pembelajaran, 2025)
This research aims to develop comic-based learning media to improve students' creative thinking skills in Indonesian language subjects in junior high school. This study employed the research and development method with the ADDIE model (analysis, design, development, implementation, and evaluation). The instruments included observation questionnaires, interviews, and feasibility and effectiveness assessments. Data analysis techniques used were descriptive qualitative and quantitative. The study's results are as follows: (1) Initial observations highlighted the need for developing learning media in class VII SMP/MTs, which served as the basis for product development; (2) The design stage involved creating learning media components ready for development; (3) The development stage produced comic-based learning media tested by several experts and students, along with an effectiveness test; (4) Material expert tests scored 3.80, media expert tests scored 4.00, indicating good quality. Student feasibility tests calculated using the AIKEN V formula scored 0.95 to 1, categorized as very good. An experimental test was conducted on 20 students in control and experimental classes. The independent sample test analysis yielded a p-value of 0.154, indicating that the p-value > 0.05, thus H0 was accepted. Therefore, the comic products developed are effective in improving students' creative thinking skills. This research is expected to provide references for learning media that enhance creative literacy, leading to students' creative thinking skills, an essential competency in the 21st century.